Positive electrode active material for non-aqueous electrolyte secondary battery
By treating lithium-nickel composite oxide with boron, phosphorus, or silicon to form a surface region, the positive electrode active material for non-aqueous electrolyte secondary batteries enhances resistance to high temperature and humidity, maintaining high charge/discharge capacity and reducing resistance.
Patent Information
- Application Number
- JP2021207173
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-21
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2036-07-20
AI Technical Summary
Existing positive electrode active materials for non-aqueous electrolyte secondary batteries deteriorate in charge/discharge characteristics due to exposure to high temperature and high humidity environments, leading to issues such as surface degradation and reduced cycle life.
A positive electrode active material with a lithium-nickel composite oxide structure (Li x Ni 1-y-z Co y Al z O 2) is treated with boron, phosphorus, or silicon compounds to form a surface region containing these elements, maintaining a carbon content of 0.06% by mass or less, enhancing resistance to environmental degradation.
The treated material maintains high charge/discharge capacity and reduces positive electrode resistance, even when exposed to high temperature and humidity, thereby improving the battery's durability and performance.
Smart Images

Figure 0007612562000003 
Figure 0007612562000004 
Figure 0007612562000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a non-aqueous electrolyte secondary battery, and a method for producing the positive electrode active material for a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In recent years, with the widespread use of portable electronic devices such as mobile phones and notebook computers, there has been a strong demand for the development of small, lightweight non-aqueous electrolyte secondary batteries with high energy density, as well as high-output secondary batteries for use in electric vehicles, including hybrid vehicles.
[0003] A lithium-ion secondary battery is a non-aqueous electrolyte secondary battery that meets these requirements. A lithium-ion secondary battery has a cell structure that is composed of a positive electrode, a negative electrode, an electrolyte, and a separator as basic elements, and the positive electrode and the negative electrode use active materials (positive electrode active material, negative electrode active material) that can extract and insert lithium.
[0004] The positive electrode active material used in the positive electrode is usually a composite oxide containing lithium and a transition metal. Specifically, lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) are layered materials, lithium manganese oxide (LiMn2O4) is a spinel material, and lithium iron phosphate (LiFePO4) is an olivine material. Furthermore, in order to achieve high energy density, lithium manganese nickel oxide (LiMnO2) is a spinel material that is charged and discharged at a high voltage (5V class). 3 / 2 Ni 1 / 2 Development is also being conducted on manganese-containing lithium composite oxides (e.g., Li2MnO3-LiMO2 [M: Ni, Mn, Co, etc.]) that are solid solution systems (also called "excess systems") as layered materials with high capacity (e.g., Li2MnO3-LiMO2 [M: Ni, Mn, Co, etc.]).
[0005] Among the above positive electrode active materials, lithium cobalt oxide is widely used mainly in portable electronic devices because it can achieve a high voltage of about 4V and has relatively excellent charge / discharge and cycle characteristics. However, the high cost of cobalt and its large price fluctuations are issues, and lithium nickel oxide and lithium manganese oxide, which use nickel and manganese that are cheaper than cobalt, are attracting attention.
[0006] However, although lithium manganate has superior thermal stability to lithium cobalt oxide, its charge / discharge capacity is smaller than other positive electrode active materials. In addition, repeated charge / discharge cycles cause manganese to dissolve into the electrolyte, resulting in a decline in cycle characteristics. These drawbacks mean that there are many issues with its practical use as a lithium-ion secondary battery.
[0007] On the other hand, lithium nickel oxide has a larger charge / discharge capacity than lithium cobalt oxide, but has the disadvantage of being inferior to lithium cobalt oxide in terms of thermal stability and cycle characteristics. Therefore, lithium nickel composite oxides have been developed in which part of the nickel in lithium nickel oxide is replaced with other elements, improving thermal stability and cycle characteristics. Specifically, lithium nickel cobalt aluminum oxide (LiNi X Co y Al Z O2, x+y+z=1), lithium nickel cobalt manganese oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) etc.
[0008] However, the above-mentioned positive electrode active material, when exposed to a high-temperature and high-humidity environment, for example, is deteriorated due to reaction with moisture in the air, carbon dioxide, etc., and when used as a positive electrode of a lithium-ion secondary battery, there is a problem that the charge-discharge characteristics and cycle characteristics are deteriorated. In addition, when the positive electrode active material is used as a positive electrode of a lithium-ion secondary battery, the surface of the positive electrode active material is deteriorated due to reaction with the electrolyte or elution of metal ions into the electrolyte, etc., and the charge-discharge characteristics and cycle characteristics are deteriorated.
[0009] In order to solve the above problems, methods have been attempted in which the positive electrode active material is subjected to a surface treatment to suppress deterioration due to contact with moisture and carbon dioxide contained in the air, and in the case of using the positive electrode active material as the positive electrode of a lithium ion secondary battery, suppresses surface deterioration of the positive electrode active material due to contact with an electrolyte.
[0010] For example, Patent Document 1 discloses a method for producing a positive electrode active material for a nonaqueous electrolyte secondary battery, in which a gaseous metal halide is brought into contact with a lithium-containing composite oxide to coat at least a part of the surface of the lithium-containing composite oxide with the metal halide.
[0011] However, gaseous metal halides are corrosive and react with moisture in the air to produce hydrofluoric acid (HF) or hydrochloric acid (HCl), so this method of forming a coating is not ideal from the standpoint of safety.
[0012] Patent Document 2 discloses a method for producing lithium composite compound particles, which comprises: adding sulfate, nitrate, hydrochloride, oxalate, or alkoxide of the A element as the A raw material to an aqueous suspension containing a composite oxide made of lithium and a transition metal element (TM) as core particles; and using a fluorine-containing solution as a neutralizing agent to precipitate a surface treatment component containing at least the A element and fluorine on the particle surfaces of the composite oxide made of lithium and a transition metal element (TM) in an addition ratio of the metal salt of the A element to fluorine of 1:k (valence of the A element≦k≦valence of the A element×2), and then heat-treating the particles at a temperature range of 300 to 700° C. in an oxygen atmosphere.
[0013] However, when preparing an aqueous suspension containing a composite oxide consisting of lithium and a transition metal element (TM) as a core particle, the lithium on the surface of the composite oxide consisting of lithium and a transition metal element (TM) may dissolve into the water, which may result in a decrease in the charge / discharge capacity.
[0014] Furthermore, even when a positive electrode active material for a non-aqueous electrolyte secondary battery is produced by the production methods disclosed in Patent Documents 1 and 2, the degree of suppression of deterioration of charge-discharge characteristics due to exposure to a high-temperature and high-humidity environment is not sufficient. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] JP 2008-251480 A [Patent Document 2] JP 2013-232438 A Summary of the Invention [Problem to be solved by the invention]
[0016] In view of the problems associated with the above-mentioned conventional techniques, an object of one aspect of the present invention is to provide a positive electrode active material for a non-aqueous electrolyte secondary battery that can suppress deterioration of charge / discharge characteristics due to exposure to a high-temperature and high-humidity environment. [Means for solving the problem]
[0017] In order to solve the above problems, according to one aspect of the present invention, a compound having the general formula: Li x Ni 1―y―z Co y Al z Particles of a lithium nickel composite oxide represented by O2 (0.90≦x≦1.20, 0.01≦y≦0.20, 0.01≦z≦0.10), and The lithium nickel composite oxide particle has a region disposed on at least a portion of a surface thereof, the region containing one or more elements selected from boron (B), phosphorus (P), and silicon (Si), lithium (Li), and oxygen (O); The present invention provides a positive electrode active material for a non-aqueous electrolyte secondary battery, which has a carbon content of 0.06 mass % or less and a boron (B) content of 0.01 mass % or more and 0.10 mass % or less. Effect of the Invention
[0018] According to one aspect of the present invention, it is possible to provide a positive electrode active material for a non-aqueous electrolyte secondary battery that can suppress deterioration of charge-discharge characteristics due to exposure to a high-temperature and high-humidity environment. [Brief description of the drawings]
[0019] [Figure 1] FIG. 2 is an explanatory diagram of a reaction apparatus used in a contact step according to an embodiment of the present invention. [Diagram 2] 4 is an SEM image of particles of the lithium nickel composite oxide used in the examples and comparative examples. [Diagram 3] 4 is an SEM image of the lithium nickel composite oxide particles after the contact step according to Example 1. [Figure 4] 4 is an SEM image of the lithium nickel composite oxide particles after the heat treatment step according to Example 1. [Diagram 5] FIG. 1 is an explanatory diagram of a Nyquist plot and an equivalent circuit used in fitting calculations. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, the form for carrying out the present invention will be described with reference to the drawings. However, the present invention is not limited to the following embodiment, and various modifications and substitutions can be made to the following embodiment without departing from the scope of the present invention. [Cathode active material] An example of the configuration of the positive electrode active material for a non-aqueous electrolyte secondary battery according to this embodiment will be described below.
[0021] The positive electrode active material for a non-aqueous electrolyte secondary battery according to the present embodiment is represented by the general formula: Li x Ni 1―y―z Co y Al zThe positive electrode active material for a non-aqueous electrolyte secondary battery of this embodiment can have a carbon content of 0.06 mass % or less.
[0022] The positive electrode active material for a non-aqueous electrolyte secondary battery according to the present embodiment (hereinafter, also simply referred to as the “positive electrode active material”) is represented by the general formula: Li x Ni 1―y―z Co y Al z The lithium nickel composite oxide particles may be represented by the formula: O2 (0.90≦x≦1.20, 0.01≦y≦0.20, 0.01≦z≦0.10).
[0023] In the above general formula, the atomic ratio x indicating the content of lithium (Li) is preferably in the range of 0.90≦x≦1.20, and more preferably 0.95≦x≦1.15. This is because if the atomic ratio x is less than 0.90, the charge / discharge capacity of the secondary battery may decrease, and if the atomic ratio x exceeds 1.20, the thermal stability of the secondary battery may decrease.
[0024] In the above general formula, the atomic ratio y, which indicates the content of cobalt (Co), is preferably in the range of 0.01≦y≦0.20, and more preferably 0.03≦y≦0.15. This is because if the atomic ratio y is less than 0.01, the cycle characteristics of the secondary battery may be insufficient, and if the atomic ratio y exceeds 0.20, the charge / discharge capacity of the secondary battery may decrease due to a decrease in the nickel content.
[0025] Furthermore, in the above general formula, the range of the atomic ratio z, which indicates the content of aluminum (Al), is preferably 0.01≦z≦0.10, and more preferably 0.01≦z≦0.05. This is because if the atomic ratio z is less than 0.01, the thermal stability of the secondary battery may decrease, and if the atomic ratio z exceeds 0.10, the secondary battery may not be solid-dissolved in the positive electrode active material, resulting in the generation of a different phase, thereby decreasing the charge / discharge capacity of the secondary battery.
[0026] In the above general formula, the atomic ratio 1-yz, which indicates the content of nickel (Ni), is preferably in the range of 0.70 to 0.98, more preferably in the range of 0.80 to 0.96. This is because if 1-yz is less than 0.70, the charge / discharge capacity of the secondary battery may decrease, and if 1-yz is more than 0.98, the thermal stability of the secondary battery may be insufficient.
[0027] The carbon content of the positive electrode active material of this embodiment can be 0.06% by mass or less. By setting the carbon content of the positive electrode active material to 0.06% by mass or less, the charge / discharge capacity can be kept high even after a weather resistance test, i.e., even after exposure to a high temperature and high humidity environment, for example, an environment with a temperature of 80° C. or more and a humidity of 60% or more.
[0028] The reason why the charge / discharge capacity can be maintained high even when exposed to a high-temperature and high-humidity environment by setting the carbon content of the positive electrode active material of this embodiment to 0.06 mass % or less is not clear, but the inventors of the present invention speculate as follows.
[0029] The positive electrode active material of this embodiment can have lithium nickel composite oxide particles as described above, and a region (hereinafter also referred to as "boron-containing region") that contains one or more elements selected from boron, phosphorus, and silicon, lithium, and oxygen, which are arranged on at least a part of the surface of the lithium nickel composite oxide particles. By setting the carbon content of the positive electrode active material of this embodiment to 0.06 mass% or less, the amount of carbon contained in the boron-containing region, more specifically the content of organic matter, can be reduced, and the boron-containing region can be densified. Therefore, even if the positive electrode active material of this embodiment is exposed to a high temperature and high humidity environment, the lithium nickel composite oxide particles are unlikely to undergo surface deterioration, a high charge / discharge capacity can be obtained, and the positive electrode resistance can be reduced.
[0030] The carbon content of the positive electrode active material of this embodiment is more preferably 0.05% by mass or less. Since the carbon content of the positive electrode active material of this embodiment is preferably low, the lower limit is not particularly limited and can be, for example, 0 or more. However, although the carbon content can be reduced by, for example, a heat treatment described later, if the heat treatment is performed for a long period of time in order to reduce the carbon content, the composition of the lithium nickel composite oxide may deviate from the target composition, so it is preferable not to reduce the carbon content excessively. For this reason, the carbon content is preferably, for example, 0.02% by mass or more.
[0031] The lithium nickel composite oxide particles contained in the positive electrode active material of this embodiment can be composed of secondary particles formed by aggregation of primary particles. The secondary particles of the lithium nickel composite oxide particles preferably have an average particle size in the range of 3 μm to 20 μm, more preferably in the range of 5 μm to 15 μm.
[0032] This is because if the average particle size of the secondary particles of the lithium nickel composite oxide particles is less than 3 μm, the packing density of the lithium nickel composite oxide particles decreases when the positive electrode is formed, resulting in a decrease in the charge / discharge capacity of the secondary battery.On the other hand, if the average particle size of the secondary particles of the lithium nickel composite oxide particles exceeds 20 μm, the contact area between the positive electrode active material and the electrolyte in the secondary battery decreases, which may result in a decrease in the charge / discharge capacity of the secondary battery.
[0033] The average particle size here means a volume-integrated average value in a particle size distribution determined by a laser diffraction / scattering method, and the term "average particle size" has the same meaning in this specification.
[0034] The positive electrode active material of this embodiment can have a region (boron-containing region) that is disposed on at least a portion of the surface of a lithium nickel composite oxide particle and contains one or more elements selected from boron (B), phosphorus (P), and silicon (Si), lithium (Li), and oxygen (O). As described above, the lithium nickel composite oxide particle can be composed of secondary particles formed by agglomeration of primary particles, and the boron-containing region can be disposed, for example, on the surface of the primary particles and secondary particles that constitute the lithium nickel composite oxide particle.
[0035] The boron-containing region needs only to be present on at least a portion of the surface of the lithium nickel composite oxide particle as a region containing lithium, oxygen, and one or more elements selected from boron, phosphorus, and silicon, and it is not necessary for a clear interface to exist between the lithium nickel composite oxide particle and the boron-containing region.
[0036] For example, the boron-containing region can be formed and arranged as a region covering a part of the surface of the lithium nickel composite oxide particle. The boron-containing region may be formed and arranged on the surface of the lithium nickel composite oxide particle as a coating covering the entire surface. In either case, when the boron-containing region is formed and arranged as a region covering a part of the surface of the lithium nickel composite oxide particle, or when the boron-containing region is formed and arranged as a coating covering the entire surface, there is no need for a clear interface to exist between the lithium nickel composite oxide particle and the boron-containing region.
[0037] However, if one or more elements selected from boron (B), phosphorus (P), and silicon (Si) are completely dissolved inside the lithium nickel composite oxide particles and there is no difference in composition between the inside of the lithium nickel composite oxide particles and the surface of the particles, the effect of obtaining high charge / discharge characteristics cannot be obtained, and the charge / discharge characteristics may be significantly reduced. Therefore, it is preferable that one or more elements selected from boron (B), phosphorus (P), and silicon (Si) are present unevenly on the surface of the lithium nickel composite oxide particles. For example, the boron-containing region may be configured to be present only on the surface of the lithium nickel composite oxide particles.
[0038] The form of the elements constituting the boron-containing region is not particularly limited. For example, in the boron-containing region, the lithium component (lithium hydroxide, lithium carbonate, etc.) present on the particle surface of the lithium nickel composite oxide reacts with one or more elements selected from boron, phosphorus, and silicon to form a form having Li-OB bond, Li-OP bond, Li-O-Si bond, etc.
[0039] As described above, the positive electrode active material of this embodiment is arranged on at least a part of the surface of the lithium nickel composite oxide particles, and can have a region containing one or more elements selected from boron, phosphorus, and silicon, lithium, and oxygen, i.e., a boron-containing region. Therefore, the positive electrode active material of this embodiment can contain one or more elements selected from boron, phosphorus, and silicon. In this case, the content of one or more elements selected from boron, phosphorus, and silicon is not particularly limited, and can be arbitrarily selected depending on, for example, the environment in which the positive electrode active material of this embodiment is used or the environment in which it is stored.
[0040] For example, when the positive electrode active material of the present embodiment contains boron, the content of boron (B) in the positive electrode active material of the present embodiment is preferably 0.01% by mass or more and 0.10% by mass or less. This is because, for example, when the positive electrode active material of the present embodiment is applied to a paste for forming a positive electrode active material layer of a non-aqueous electrolyte secondary battery, if the content of boron is in the above range, it is possible to improve the stability of the paste for forming a positive electrode active material layer (suppress gelation) without impairing the battery characteristics, which is preferable.
[0041] In addition, when the positive electrode active material of this embodiment contains phosphorus, the content of phosphorus (P) in the positive electrode active material of this embodiment is preferably 0.01% by mass or more and 0.10% by mass or less. This is because, for example, when the positive electrode active material of this embodiment is applied to a paste for forming a positive electrode active material layer of a non-aqueous electrolyte secondary battery, if the content of phosphorus is in the above range, it is possible to improve the stability of the paste for forming a positive electrode active material layer (suppress gelation) without impairing the battery characteristics, which is preferable.
[0042] In addition, when the positive electrode active material of this embodiment contains silicon, the silicon (Si) content of the positive electrode active material of this embodiment is preferably 0.05 mass% or more and 0.30 mass% or less. This is because, for example, when the positive electrode active material of this embodiment is applied to a paste for forming a positive electrode active material layer of a non-aqueous electrolyte secondary battery, if the silicon content is in the above range, it is possible to improve the stability (suppress gelation) of the paste for forming a positive electrode active material layer without impairing the battery characteristics, which is preferable.
[0043] The positive electrode active material for a non-aqueous electrolyte secondary battery of the present embodiment described above can have a region disposed on at least a part of the surface of a particle of a lithium nickel composite oxide, containing one or more elements selected from boron (B), phosphorus (P), and silicon (Si), lithium (Li), and oxygen (O). Also, the carbon content can be 0.06 mass% or less.
[0044] Therefore, the positive electrode active material for a non-aqueous electrolyte secondary battery of this embodiment can be a positive electrode active material for a non-aqueous electrolyte secondary battery that can suppress deterioration of charge-discharge characteristics due to exposure to a high-temperature and high-humidity environment. That is, even if the positive electrode active material for a non-aqueous electrolyte secondary battery of this embodiment is exposed to a high-temperature and high-humidity environment and then a secondary battery is formed using the positive electrode active material as a positive electrode material, the positive electrode active material can exhibit high charge-discharge characteristics.
[0045] Furthermore, the positive electrode active material for a non-aqueous electrolyte secondary battery of this embodiment can be suitably used as a positive electrode for a secondary battery. [Method of manufacturing positive electrode active material for non-aqueous electrolyte secondary battery] Next, a description will be given of one configuration example of the method for producing the positive electrode active material for a non-aqueous electrolyte secondary battery according to this embodiment.
[0046] The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to this embodiment (hereinafter also simply referred to as a "method for producing a positive electrode active material") may include the following steps.
[0047] General formula: Li x Ni 1―y―z Co yAl z A contacting step of contacting particles of a lithium nickel composite oxide represented by O2 (0.90≦x≦1.20, 0.01≦y≦0.20, 0.01≦z≦0.10) with a gas containing one or more compounds selected from boron compounds, phosphorus compounds, and silicon compounds. A heating step in which the material obtained after the contacting step is heat-treated at a temperature of 600°C or higher and 800°C or lower.
[0048] The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to the present embodiment can produce the positive electrode active material for a non-aqueous electrolyte secondary battery described above, and therefore some of the matters already described will not be described again.
[0049] Each step will now be described in detail. (a) Contact process In the contact step, the lithium nickel composite oxide particles can be contacted with a gas containing vapor of one or more compounds selected from a boron compound, a phosphorus compound, and a silicon compound. By carrying out the contact step, a boron-containing region can be formed on the surface of the lithium nickel composite oxide particles.
[0050] When a boron compound is used in the contact step, the boron compound is not particularly limited, but is preferably a volatile boron compound, more preferably a boron compound having a boiling point of 300° C. or less, and even more preferably an alkyl borate having a boiling point of 250° C. or less.
[0051] The above boiling point means the boiling point under atmospheric pressure (101.325 kPa), and hereinafter in this specification, unless otherwise specified, the boiling point means the boiling point under atmospheric pressure.
[0052] As the boron compound used in the contact step, for example, one or more compounds selected from trimethyl borate (trimethoxyborane) [B(OCH3)3] having a boiling point of 68°C and triethyl borate (triethoxyborane) [B(OC2H5)3] having a boiling point of 120°C can be particularly preferably used.
[0053] When a phosphorus compound is used in the contact step, the compound is not particularly limited, but is preferably a volatile phosphorus compound, more preferably a phosphorus compound having a boiling point of 300°C or less, and even more preferably an alkyl phosphoric acid having a boiling point of 250°C or less.
[0054] As the phosphorus compound used in the contact step, for example, one or more selected from trimethyl phosphite (trimethoxyphosphine) [P(OCH3)3] having a boiling point of 111°C, triethyl phosphite (triethoxyphosphine) [P(OC2O5)3] having a boiling point of 156°C, trimethyl phosphate (trimethoxyphosphine oxide) [P(O)(OCH3)3] having a boiling point of 197°C, triethyl phosphate (triethoxyphosphine oxide) [P(O)(OC2H5)3] having a boiling point of 215°C, and dimethyl phosphate (dimethyl phosphate) [P(O)(OH)(OCH3)2] having a boiling point of 174°C can be particularly preferably used.
[0055] When a silicon compound is used in the contact step, the silicon compound is not particularly limited, but is preferably a volatile silicon compound, more preferably a silicon compound having a boiling point of 300°C or less, and even more preferably an alkylsilicic acid having a boiling point of 250°C or less.
[0056] Examples of silicon compounds used in the contact step include dimethoxydimethylsilane [Si(CH3)2(OCH3)2] with a boiling point of 81°C, trimethoxysilane [Si(H)(OCH3)3] with a boiling point of 83°C, trimethoxymethylsilane [Si(CH3)(OCH3)3] with a boiling point of 103°C, tetramethyl orthosilicate (tetramethoxysilane) [Si(OCH3)4] with a boiling point of 122°C, vinyltrimethylsilane [Si(OCH3)5] with a boiling point of 123°C, and tetramethylsilane [Si(OCH3)6] with a boiling point of 123°C. Particularly preferred are one or more selected from the group consisting of methoxysilane [Si(C2H3)(OCH3)3], triethoxymethylsilane [Si(CH3)(OC2H5)3] having a boiling point of 143°C, tetraethyl orthosilicate (tetraethoxysilane) [Si(OC2H5)4] having a boiling point of 165°C, and 3-aminopropyltrimethoxysilane [Si(C3H6NH2)(OCH3)3] having a boiling point of 92°C at 2 kPa.
[0057] 1, for example, a first storage container 3 for storing lithium nickel composite oxide particles and a second storage container 5 for storing one or more compounds selected from boron compounds, phosphorus compounds, and silicon compounds are placed in a reaction container 1. Then, lithium nickel composite oxide particles 2 and one or more compounds 4 selected from boron compounds, phosphorus compounds, and silicon compounds are placed in each storage container, and the contact step can be carried out by leaving the particles as they are in the atmospheric gas or by rotating a fan 6.
[0058] When multiple types of compounds are used as one or more compounds selected from boron compounds, phosphorus compounds, and silicon compounds, multiple second storage containers 5 can be installed according to the number of types of the compounds. Also, multiple types of compounds can be mixed and installed in the second storage container 5.
[0059] The reaction vessel 1 is preferably a highly airtight vessel so that the vapor of the one or more compounds selected from the atmospheric gas, boron compounds, phosphorus compounds, and silicon compounds does not leak to the outside. The material of the reaction vessel 1 is not particularly limited as long as it does not react with the vapor of the one or more compounds selected from the boron compounds, phosphorus compounds, and silicon compounds. Examples of the material of the reaction vessel 1 include plastics such as polyethylene, polypropylene, and Teflon (registered trademark); ceramics such as alumina, quartz, and glass; and metals such as stainless steel (SUS304, SUS316, etc.) and titanium.
[0060] The first storage container 3 and the second storage container 5 are also not particularly limited as long as they do not react with the lithium nickel composite oxide particles 2, the one or more compounds 4 selected from a boron compound, a phosphorus compound, and a silicon compound, and have durability. For example, they can be arbitrarily selected depending on the types of the lithium nickel composite oxide particles 2, the one or more compounds 4 selected from a boron compound, a phosphorus compound, and a silicon compound used, etc.
[0061] Examples of materials for the first storage container 3 and the second storage container 5 include plastics such as polyethylene, polypropylene, and Teflon; ceramics such as alumina, quartz, and glass; and metals such as stainless steel and titanium.
[0062] The atmospheric gas in the reaction vessel 1 is not particularly limited, and can be arbitrarily selected depending on the type of the lithium nickel composite oxide particles 2 and the one or more compounds 4 selected from boron compounds, phosphorus compounds, and silicon compounds used. However, it is preferable that the atmospheric gas in the reaction vessel 1 is a gas that does not react with the lithium nickel composite oxide particles 2 and the one or more compounds 4 selected from boron compounds, phosphorus compounds, and silicon compounds. Examples of the atmospheric gas in the reaction vessel 1 include air, nitrogen, and argon.
[0063] In addition, carbon dioxide gas (CO2) and moisture (H2O) generally react easily with the lithium nickel composite oxide particles 2 and one or more compounds 4 selected from boron compounds, phosphorus compounds, and silicon compounds. For this reason, it is preferable to use an atmospheric gas with a low content of carbon dioxide gas or moisture.
[0064] Therefore, the atmospheric gas in the reaction vessel 1 is preferably a gas selected from, for example, dry air, dry air treated with decarbonation gas, high-purity nitrogen, high-purity argon, and the like.
[0065] The dry air preferably has a dew point temperature of -30°C or lower, and more preferably -50°C or lower.
[0066] Furthermore, the high purity nitrogen preferably has a nitrogen content of more than 99.9995 vol.%, and more preferably has a nitrogen content of more than 99.9998 vol.%, and the high purity argon preferably has an argon content of more than 99.999 vol.%, and more preferably has a nitrogen content of more than 99.9995 vol.%, for example.
[0067] Depending on the type of one or more compounds 4 selected from boron compounds, phosphorus compounds, and silicon compounds, when air or the like is used as the atmospheric gas, there may be a risk of explosion or oxidation deterioration due to oxygen depending on the mixing ratio of the atmospheric gas and the vapor of one or more compounds selected from boron compounds, phosphorus compounds, and silicon compounds. Therefore, in such cases, it is preferable to use nitrogen or argon as the atmospheric gas instead of air.
[0068] As described above, the atmospheric gas in the reaction vessel 1 is not particularly limited, and can be selected according to the type of one or more compounds 4 selected from boron compounds, phosphorus compounds, and silicon compounds to be used.
[0069] Then, as described above, each raw material is placed in the first storage container 3 and the second storage container 5 inside the reaction container 1, and the atmosphere inside the reaction container 1 is replaced with a specified atmospheric gas. After that, the atmosphere inside the reaction container 1 is made uniform by leaving it as it is or by rotating the fan 6, and the contacting step can be carried out.
[0070] In the reaction vessel 1, when the reaction vessel 1 is left as it is or when the fan 6 is rotated, the vapor of one or more compounds 4 selected from a boron compound, a phosphorus compound, and a silicon compound diffuses from the second storage vessel 5 into the atmospheric gas. Then, the vapor of one or more compounds 4 selected from a boron compound, a phosphorus compound, and a silicon compound diffused into the atmospheric gas comes into contact with the surface of the lithium nickel composite oxide particles 2 in the first storage vessel 3 and is consumed. Therefore, as the reaction time passes, the one or more compounds 4 selected from a boron compound, a phosphorus compound, and a silicon compound initially stored in the second storage vessel 5 undergo mass transfer into the first storage vessel 3.
[0071] The amount of one or more elements selected from boron, phosphorus, and silicon contained in at least a part of the surface of the lithium nickel composite oxide particles and the method for controlling the thickness of the boron-containing region are not particularly limited. For example, they can be controlled by the following methods.
[0072] One control method is a method of controlling by the amount of raw materials stored in each storage container of the reaction container 1. First, a predetermined amount of lithium nickel composite oxide particles 2 and one or more compounds 4 selected from boron compounds, phosphorus compounds, and silicon compounds are placed in the first storage container 3 and the second storage container 5 in the reaction container 1. However, at this time, the amount of the lithium nickel composite oxide particles 2 and the one or more compounds 4 selected from boron compounds, phosphorus compounds, and silicon compounds placed in each storage container is adjusted to an amount according to the amount of one or more elements selected from boron, phosphorus, and silicon contained in the lithium nickel composite oxide particles to be produced, the thickness of the boron-containing region, etc. Then, the reaction can be controlled by replacing the inside of the reaction container 1 with an atmospheric gas, leaving it as it is, or rotating the fan 6 to terminate the reaction when the one or more compounds 4 selected from boron compounds, phosphorus compounds, and silicon compounds in the second storage container 5 have completely disappeared.
[0073] Another control method is a method of controlling by the reaction time in the reaction vessel 1. In this case, first, a predetermined amount of the lithium nickel composite oxide particles 2 and one or more compounds 4 selected from a boron compound, a phosphorus compound, and a silicon compound are placed in the first storage container 3 and the second storage container 5 in the reaction vessel 1. However, at this time, the amount of the one or more compounds 4 selected from a boron compound, a phosphorus compound, and a silicon compound placed in the second storage container 5 is stored so as to be in excess compared with the amount of one or more elements selected from boron, phosphorus, and silicon contained in the lithium nickel composite oxide particles to be produced, and the amount according to the thickness of the boron-containing region, etc. Then, after replacing the inside of the reaction vessel 1 with an atmospheric gas, the reaction vessel 1 is left as it is, or the fan 6 is rotated, and when a predetermined time has elapsed, the second storage container 5 is removed from the reaction vessel 1 while a part of the one or more compounds 4 selected from a boron compound, a phosphorus compound, and a silicon compound remains, and the reaction can be controlled by terminating the reaction.
[0074] Although the contact step has been described above using an example in which the reaction apparatus shown in Fig. 1 is used, the reaction apparatus used in the contact step is not limited to the example shown in Fig. 1. Various reaction apparatuses can be used as long as they are capable of contacting the particles of the lithium nickel composite oxide with the vapor of one or more compounds selected from boron compounds, phosphorus compounds, and silicon compounds. (b) Heating process In the heating step, the material obtained in the contacting step, i.e., particles of lithium nickel composite oxide contacted with one or more compounds selected from boron compounds, phosphorus compounds, and silicon compounds, can be placed in an atmospheric furnace and heated.
[0075] By carrying out the heating step, it is possible to remove organic components and trace amounts of moisture contained in one or more compounds selected from boron compounds, phosphorus compounds, and silicon compounds that are brought into contact with the surfaces of the lithium nickel composite oxide particles in the contacting step, and it is possible to increase the crystallinity and denseness of a region (boron-containing region) that contains one or more elements selected from boron, phosphorus, and silicon, lithium, and oxygen and that is arranged on at least a portion of the surface of the lithium nickel composite oxide particles.
[0076] The furnace used in the heating step, for example, an electric furnace, is not particularly limited, but is preferably a furnace capable of controlling the atmosphere during the heat treatment, for example, an atmospheric furnace, a tubular furnace, a pusher furnace, a roller hearth furnace, etc.
[0077] The heating temperature in the heating step is preferably 600°C or higher and 800°C or lower, and more preferably 650°C or higher and 750°C or lower.
[0078] This is because if the heating temperature is less than 600° C., there is a risk that organic components and trace amounts of moisture contained in one or more compounds selected from boron compounds, phosphorus compounds, and silicon compounds may not be sufficiently reduced or removed. Also, if the heating temperature is more than 800° C., sintering of the particles of the lithium nickel composite oxide proceeds, reducing the specific surface area, and when used as a secondary battery, the contact area with the electrolyte is reduced, which may result in a reduced charge / discharge capacity.
[0079] The atmosphere used in the heating step is not particularly limited. For example, a vacuum atmosphere or a gas that does not react with one or more compounds selected from boron compounds, phosphorus compounds, and silicon compounds arranged on the surface of the lithium nickel composite oxide or lithium nickel oxide particles used can be preferably used. The atmospheric gas used in the heating step is preferably one having an oxygen concentration of 60% by volume or more and a carbon dioxide (CO2) partial pressure of 10 Pa or less. This is because if the oxygen concentration is less than 60%, nickel (Ni) in the lithium nickel composite oxide is reduced, and the charge / discharge capacity may decrease when used as a secondary battery, and if the carbon dioxide partial pressure is higher than 10 Pa, the carbon dioxide gas may react with lithium in the lithium nickel composite oxide and the charge / discharge capacity may decrease when used as a secondary battery.
[0080] The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to this embodiment may include any step other than the above-mentioned contact step and heating step.
[0081] For example, it may have a lithium nickel composite oxide production process for producing lithium nickel composite oxide particles to be subjected to the contact process. The specific steps of the lithium nickel composite oxide production process are not particularly limited, and may be any steps capable of producing lithium nickel composite oxide particles. The lithium nickel composite oxide production process may have, for example, the following steps.
[0082] A crystallization step in which water is added to a reaction tank and stirred while controlling the pH value in the tank to between 11 and 13. At the same time, a mixed aqueous solution of nickel sulfate, cobalt sulfate, and aluminum sulfate, an aqueous sodium hydroxide solution, and an aqueous ammonia solution are added to obtain nickel composite hydroxide particles. A roasting step in which the nickel composite hydroxide particles are roasted at a temperature of 500° C. or higher and 700° C. or lower to obtain a nickel composite oxide. A calcination step of mixing the nickel composite oxide with lithium hydroxide monohydrate and calcining the mixture at a temperature of 650° C. or higher and 850° C. or lower to obtain a lithium nickel composite oxide. A crushing step of crushing the lithium nickel composite oxide.
[0083] Note that, here, the optional steps have been described using the lithium nickel composite oxide manufacturing process as an example, but the method for manufacturing a positive electrode active material of the present embodiment is not limited to the above-mentioned example steps, and may include various optional steps as necessary.
[0084] The positive electrode active material for non-aqueous electrolyte secondary batteries obtained by the method for producing a positive electrode active material for non-aqueous electrolyte secondary batteries according to the present embodiment described above can have a region that is arranged on at least a part of the surface of a particle of lithium nickel composite oxide and contains one or more elements selected from boron (B), phosphorus (P), and silicon (Si), lithium (Li), and oxygen (O). Also, the carbon content can be 0.06 mass% or less.
[0085] Therefore, the positive electrode active material for a non-aqueous electrolyte secondary battery obtained by the manufacturing method of the positive electrode active material for a non-aqueous electrolyte secondary battery of this embodiment can be a positive electrode active material for a non-aqueous electrolyte secondary battery that can suppress the deterioration of the charge-discharge characteristics caused by exposure to a high-temperature and high-humidity environment. That is, even if the positive electrode active material for a non-aqueous electrolyte secondary battery is exposed to a high-temperature and high-humidity environment and then a secondary battery is formed using the positive electrode active material as a positive electrode material, the positive electrode active material can exhibit high charge-discharge characteristics.
[0086] Furthermore, the positive electrode active material for a non-aqueous electrolyte secondary battery obtained by the method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery of this embodiment can be suitably used as a positive electrode for a secondary battery.
[0087] In addition, the method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery of this embodiment uses a simple production method in which an atmospheric gas containing one or more compounds selected from a boron compound, a phosphorus compound, and a silicon compound is brought into contact with the surface of a lithium nickel composite oxide particle and heated. Therefore, a positive electrode active material for a non-aqueous electrolyte secondary battery having resistance to high temperature and high humidity environments can be produced at low cost, which is industrially useful. EXAMPLES
[0088] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.
[0089] The preparation conditions and evaluation results of the samples in each of the examples and comparative examples will be described below. [Example 1] A positive electrode active material for a non-aqueous electrolyte secondary battery was produced and evaluated according to the following procedure. (1) Manufacturing method of positive electrode active material for non-aqueous electrolyte secondary battery (Lithium nickel composite oxide manufacturing process) First, water was placed in a reaction tank and the temperature inside the tank was set to 50°C while stirring. A mixed aqueous solution of nickel sulfate, cobalt sulfate, and aluminum sulfate (metal element molar ratio Ni:Co:Al = 82:15:3), a 25 mass% aqueous sodium hydroxide solution, and a 25 mass% aqueous ammonia solution were simultaneously added to the reaction tank. Crystallization was carried out for 11 hours while controlling the pH value inside the reaction tank to 11.5 based on a liquid temperature of 25°C, to produce nickel composite hydroxide particles (crystallization step).
[0090] After the crystallization step was completed, the product was roasted at 600° C. in an air atmosphere to obtain nickel composite oxide particles (roasting step).
[0091] The nickel composite oxide particles obtained in the roasting step were mixed with lithium hydroxide monohydrate, and the mixture obtained was pre-calcined in an oxygen atmosphere at 500°C for 3 hours, and then calcined at 750°C for 20 hours (calcination step). When preparing the mixture, the nickel composite oxide particles and lithium hydroxide monohydrate were weighed and mixed so that the metal element molar ratio was Li / (Ni+Co+Al)=1.02.
[0092] The product obtained in the calcination step is crushed to obtain lithium nickel composite oxide particles (Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O2) was obtained (disintegration step).
[0093] The particle shape of the obtained lithium nickel composite oxide particles was observed using a scanning electron microscope (SEM) (manufactured by JEOL Ltd., model number: JSM-7100F). The photograph taken is shown in Figure 2. It was confirmed that the obtained lithium nickel composite oxide particles consisted of secondary particles formed by the aggregation of primary particles.
[0094] Furthermore, the average particle size of the resulting lithium nickel composite oxide particles (secondary particles) was evaluated by a laser diffraction scattering method and found to be 12.0 μm.
[0095] The same lithium nickel composite oxide particles are used in the other examples and comparative examples described below. (contact process) The contacting step was carried out using the reaction apparatus shown in FIG.
[0096] In the first storage container 3, 204.0 g of the lithium nickel composite oxide particles obtained in the lithium nickel composite oxide production process were placed as the lithium nickel composite oxide particles 2. In addition, in the second storage container 5, 2.4 g of trimethyl borate (trimethoxyborane) [B(OCH3)3] was placed as one or more compounds 4 selected from boron compounds, phosphorus compounds, and silicon compounds. Then, each storage container containing the raw materials was placed in the reaction container 1, and the reaction container 1 was sealed.
[0097] The reaction vessel 1, the first storage vessel 3, and the second storage vessel 5 were all made of stainless steel.
[0098] The inside of the reaction vessel 1 was replaced and filled with nitrogen gas (dew point temperature: -50°C or lower) having a nitrogen content of more than 99.9995 vol.%, which was the atmospheric gas, and then the reaction vessel 1 was left at room temperature (25°C) while rotating the fan 6 to circulate the atmospheric gas inside the reaction vessel 1. This caused the atmospheric gas containing trimethyl borate vapor to come into contact with the surfaces of the lithium nickel composite oxide particles 2.
[0099] When the lithium nickel composite oxide particles after the contact step were analyzed by ICP emission spectrometry, it was confirmed that the particles contained 0.05 mass % of boron (B), which is a trimethyl borate component.
[0100] Furthermore, when the surface shape of the lithium nickel composite oxide was observed with a scanning electron microscope (SEM), it was confirmed that a region containing boron, lithium, and oxygen was uniformly formed on the surface of the lithium nickel composite oxide particles, as shown in Figure 3. In other words, it was confirmed that a region containing boron, lithium, and oxygen was formed as a coating covering the lithium nickel composite oxide particles on the surface of the lithium nickel composite oxide particles. (Heating process) Next, the lithium nickel composite oxide that had been subjected to the contact step was heated in an oxygen stream at 700° C. for 1 hour, and then cooled to room temperature to obtain a positive electrode active material for a non-aqueous electrolyte secondary battery according to Example 1. The oxygen gas used had an oxygen content of about 100% by volume and a carbon dioxide partial pressure of 10 Pa or less, and this was also the case in Example 2 and Comparative Example 4 below.
[0101] When the surface shape of the obtained positive electrode active material for a non-aqueous electrolyte secondary battery was observed with a scanning electron microscope (SEM), it was confirmed that there was no sintering between the primary particles and that the surface shape before the heating step was maintained, as shown in Figure 4. Therefore, it was confirmed that, similar to before the heating step, a region containing boron, lithium, and oxygen was formed on the surface of the lithium nickel composite oxide particles as a coating covering the lithium nickel composite oxide particles.
[0102] The amount of carbon contained in the obtained positive electrode active material for a non-aqueous electrolyte secondary battery was measured by high-frequency combustion infrared absorption method using a carbon analyzer (manufactured by LECO, model number: CS-600) and was found to be 0.03 mass %.
[0103] In addition, the positive electrode active material for non-aqueous electrolyte secondary batteries was analyzed by ICP emission spectrometry, and it was confirmed that the boron content was 0.05 mass% and the silicon content was below the detection limit, i.e., less than 0.02 mass%. (2) Evaluation results A coin cell (positive electrode / separator and electrolyte / negative electrode) was fabricated using the positive electrode active material for non-aqueous electrolyte secondary batteries produced by the above procedure as the positive electrode, and the charge / discharge characteristics were evaluated. The cell was charged to a cutoff voltage of 4.3 V at a C rate of 0.05 C, and then discharged to a cutoff voltage of 3.0 V. The charge capacity was confirmed to be 217 mAh / g and the discharge capacity was confirmed to be 199 mAh / g. The positive electrode resistance was also measured using the coin cell. The coin cell was charged at a charging potential of 4.1 V, and a Nyquist plot as shown in Figure 5(a) was obtained by the AC impedance method using a frequency response analyzer and a potentiogalvanostat (Solartron, 1255B). Then, fitting calculations were performed using the equivalent circuit shown in Figure 5(b), and the positive electrode resistance was calculated to be 2.4 Ω.
[0104] Next, the positive electrode active material for non-aqueous electrolyte secondary batteries was placed in a Teflon container and left in a thermo-hygrostat set at a temperature of 80°C and a humidity of 60% for 24 hours to carry out a weather resistance test. Then, a coin cell (positive electrode / separator and electrolyte / negative electrode) was produced using the positive electrode active material for non-aqueous electrolyte secondary batteries after the weather resistance test as a positive electrode, and the charge / discharge characteristics were evaluated in the same manner as above, confirming that the charge capacity was 210mAh / g and the discharge capacity was 194mAh / g.
[0105] In addition, the positive electrode resistance value was calculated in the same manner as above using the produced coin cell, and it was confirmed to be 3.2 Ω.
[0106] The production conditions and evaluation results are shown in Tables 1 and 2. [Example 2] A positive electrode active material for a non-aqueous electrolyte secondary battery was produced and evaluated in the same manner as in Example 1, except that the conditions of the contact step and the heating step were changed as follows. (1) Manufacturing method of positive electrode active material for non-aqueous electrolyte secondary battery (contact process) The contact step was carried out in the same manner as in Example 1, except that the amount of lithium nickel composite oxide particles 2 placed in the first storage container 3 was 201.7 g, and 4.0 g of tetraethyl orthosilicate (tetraethoxysilane) [Si(OC2H5)4] was used as the one or more compounds 4 selected from boron compounds, phosphorus compounds, and silicon compounds placed in the second storage container 5.
[0107] When the lithium nickel composite oxide that had been subjected to the contact step was analyzed by ICP emission spectrometry, it was confirmed that the oxide contained 0.07 mass % of silicon (Si), which is a component of tetraethyl orthosilicate.
[0108] Furthermore, when the surface shape of the lithium nickel composite oxide was observed with a scanning electron microscope (SEM), it was confirmed that a region containing silicon, lithium, and oxygen was uniformly formed on the surface of the lithium nickel composite oxide particles. In other words, it was confirmed that a region containing silicon, lithium, and oxygen was formed on the surface of the lithium nickel composite oxide particles as a coating that covers the lithium nickel composite oxide particles. (Heating process) Next, the lithium nickel composite oxide that had been subjected to the above contact step was heated in an oxygen stream at 700° C. for 1 hour, and then cooled to room temperature to obtain a positive electrode active material for a non-aqueous electrolyte secondary battery.
[0109] The amount of carbon contained in the obtained positive electrode active material for a non-aqueous electrolyte secondary battery was measured by high-frequency combustion infrared absorption method using a carbon analyzer (manufactured by LECO, model number: CS-600) and was found to be 0.05% by mass.
[0110] The obtained positive electrode active material for non-aqueous electrolyte secondary batteries was also analyzed by ICP emission spectrometry, and it was confirmed that the boron content was below the detection limit, i.e., less than 0.01 mass%, and the silicon content was 0.07 mass%.
[0111] When the surface shape of the obtained positive electrode active material for non-aqueous electrolyte secondary batteries was observed with a scanning electron microscope (SEM), it was confirmed that a region containing silicon, lithium, and oxygen was uniformly formed on the surface of the lithium nickel composite oxide particles. That is, it was confirmed that a region containing silicon, lithium, and oxygen was formed on the surface of the lithium nickel composite oxide particles as a coating covering the lithium nickel composite oxide particles. (2) Evaluation results A coin cell (positive electrode / separator and electrolyte / negative electrode) was fabricated using the obtained positive electrode active material for non-aqueous electrolyte secondary batteries as the positive electrode, and the charge / discharge characteristics were evaluated. The cell was charged to a cutoff voltage of 4.3 V at a C rate of 0.05 C, and then discharged to a cutoff voltage of 3.0 V. The charge capacity was confirmed to be 218 mAh / g and the discharge capacity was confirmed to be 195 mAh / g.
[0112] In addition, the positive electrode resistance value was calculated in the same manner as above using the produced coin cell, and it was confirmed to be 2.5 Ω.
[0113] Next, the positive electrode active material for non-aqueous electrolyte secondary batteries was placed in a Teflon container and left in a thermo-hygrostat set at a temperature of 80°C and a humidity of 60% for 24 hours. A coin cell (positive electrode / separator and electrolyte / negative electrode) was fabricated using this as the positive electrode, and the charge / discharge characteristics were evaluated in the same manner as above, confirming that the charge capacity was 211 mAh / g and the discharge capacity was 192 mAh / g.
[0114] In addition, the positive electrode resistance value was calculated in the same manner as above using the produced coin cell, and it was confirmed to be 3.4 Ω.
[0115] The production conditions and evaluation results are shown in Tables 1 and 2. [Comparative Example 1] (1) Manufacturing method of positive electrode active material for non-aqueous electrolyte secondary battery A positive electrode active material for a non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the contact step and the heating step were not performed, and only the lithium nickel composite oxide production step was performed.
[0116] Therefore, in the obtained positive electrode active material for a non-aqueous electrolyte secondary battery, the surfaces of the particles of the lithium nickel composite oxide are not subjected to a coating formation treatment, and no coating is formed on the surfaces.
[0117] The amount of carbon contained in the obtained positive electrode active material for a non-aqueous electrolyte secondary battery was measured by high-frequency combustion infrared absorption method using a carbon analyzer (manufactured by LECO, model number: CS-600) and was found to be 0.09% by mass.
[0118] In addition, the positive electrode active material for non-aqueous electrolyte secondary batteries was also analyzed by ICP emission spectrometry, and it was confirmed that the boron content was below the detection limit, i.e., less than 0.01 mass%, and the silicon content was also below the detection limit, i.e., less than 0.02 mass%. (2) Evaluation results A coin cell (positive electrode / separator and electrolyte / negative electrode) was fabricated using the obtained positive electrode active material for non-aqueous electrolyte secondary batteries as the positive electrode, and the charge / discharge characteristics were evaluated. The cell was charged to a cutoff voltage of 4.3 V at a C rate of 0.05 C, and then discharged to a cutoff voltage of 3.0 V, confirming a charge capacity of 217 mAh / g and a discharge capacity of 197 mAh / g.
[0119] In addition, when the positive electrode resistance value was calculated in the same manner as above using the produced coin cell, it was confirmed to be 1.8 Ω.
[0120] Next, the positive electrode active material for non-aqueous electrolyte secondary batteries was placed in a Teflon container and left in a thermo-hygrostat set at a temperature of 80°C and a humidity of 60% for 24 hours. A coin cell (positive electrode / separator and electrolyte / negative electrode) was fabricated using this as the positive electrode, and the charge / discharge characteristics were evaluated in the same manner as above, confirming that the charge capacity was 191 mAh / g and the discharge capacity was 175 mAh / g.
[0121] In addition, when the positive electrode resistance value was calculated in the same manner as above using the produced coin cell, it was confirmed to be 3.4 Ω.
[0122] The production conditions and evaluation results are shown in Tables 1 and 2. [Comparative Example 2] (1) Manufacturing method of positive electrode active material for non-aqueous electrolyte secondary battery A positive electrode active material for a non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the heating step was not performed, and only the lithium nickel composite oxide production step and the contact step were performed.
[0123] Thus, a positive electrode active material for a non-aqueous electrolyte secondary battery was produced in which a region containing boron, lithium, and oxygen was formed on the surface of a particle of a lithium nickel composite oxide as a coating covering the particle of the lithium nickel composite oxide.
[0124] The amount of carbon contained in the obtained positive electrode active material for a non-aqueous electrolyte secondary battery was measured by high-frequency combustion infrared absorption method using a carbon analyzer (manufactured by LECO, model number: CS-600) and was found to be 0.11 mass %.
[0125] In addition, the positive electrode active material for non-aqueous electrolyte secondary batteries was analyzed by ICP emission spectrometry, and it was confirmed that the boron content was 0.05 mass% and the silicon content was below the detection limit, i.e., less than 0.02 mass%. (2) Evaluation results A coin cell (positive electrode / separator and electrolyte / negative electrode) was fabricated using the positive electrode active material for non-aqueous electrolyte secondary batteries as the positive electrode, and the charge / discharge characteristics were evaluated. The cell was charged to a cutoff voltage of 4.3 V at a C rate of 0.05 C, and then discharged to a cutoff voltage of 3.0 V. The charge capacity was confirmed to be 220 mAh / g and the discharge capacity was confirmed to be 192 mAh / g.
[0126] In addition, the positive electrode resistance value was calculated in the same manner as above using the produced coin cell, and it was confirmed to be 2.3 Ω.
[0127] Next, the positive electrode active material for non-aqueous electrolyte secondary batteries was placed in a Teflon container and left in a thermo-hygrostat set at a temperature of 80°C and a humidity of 60% for 24 hours. A coin cell (positive electrode / separator and electrolyte / negative electrode) was fabricated using this as the positive electrode, and the charge / discharge characteristics were evaluated in the same manner as above, confirming that the charge capacity was 197 mAh / g and the discharge capacity was 172 mAh / g.
[0128] In addition, when the positive electrode resistance value was calculated in the same manner as above using the produced coin cell, it was confirmed to be 4.7 Ω.
[0129] The production conditions and evaluation results are shown in Tables 1 and 2. [Comparative Example 3] (1) Manufacturing method of positive electrode active material for non-aqueous electrolyte secondary battery A positive electrode active material for a non-aqueous electrolyte secondary battery was produced in the same manner as in Example 2, except that the heating step was not performed, and only the lithium nickel composite oxide production step and the contact step were performed.
[0130] Thus, a positive electrode active material for a non-aqueous electrolyte secondary battery was produced in which a region containing silicon, lithium, and oxygen was formed on the surface of a particle of a lithium nickel composite oxide as a coating covering the particle of the lithium nickel composite oxide.
[0131] The amount of carbon contained in the obtained positive electrode active material for a non-aqueous electrolyte secondary battery was measured by high-frequency combustion infrared absorption method using a carbon analyzer (manufactured by LECO, model number: CS-600) and was found to be 0.16% by mass.
[0132] In addition, the positive electrode active material for non-aqueous electrolyte secondary batteries was analyzed by ICP emission spectrometry, and it was confirmed that the boron content was below the detection limit, i.e., less than 0.01 mass%, and the silicon content was 0.07 mass%. (2) Evaluation results A coin cell (positive electrode / separator and electrolyte / negative electrode) was fabricated using the positive electrode active material for non-aqueous electrolyte secondary batteries as the positive electrode, and the charge / discharge characteristics were evaluated. The cell was charged to a cutoff voltage of 4.3 V at a C rate of 0.05 C, and then discharged to a cutoff voltage of 3.0 V. The charge capacity was confirmed to be 221 mAh / g and the discharge capacity was confirmed to be 193 mAh / g.
[0133] In addition, when the positive electrode resistance value was calculated in the same manner as above using the produced coin cell, it was confirmed to be 2.2 Ω.
[0134] Next, the positive electrode active material for non-aqueous electrolyte secondary batteries was placed in a Teflon container and left in a thermo-hygrostat set at a temperature of 80°C and a humidity of 60% for 24 hours. A coin cell (positive electrode / separator and electrolyte / negative electrode) was fabricated using this as the positive electrode, and the charge / discharge characteristics were evaluated in the same manner as above, confirming that the charge capacity was 210 mAh / g and the discharge capacity was 185 mAh / g.
[0135] In addition, the positive electrode resistance value was calculated in the same manner as above using the produced coin cell, and it was confirmed to be 3.7 Ω.
[0136] The production conditions and evaluation results are shown in Tables 1 and 2. [Comparative Example 4] (1) Manufacturing method of positive electrode active material for non-aqueous electrolyte secondary battery A positive electrode active material for a non-aqueous electrolyte secondary battery was produced in the same manner as in Example 2, except that in the heating step, heating was performed in an oxygen stream at 500° C. for 1 hour.
[0137] Thus, a positive electrode active material for a non-aqueous electrolyte secondary battery was produced in which a region containing silicon, lithium, and oxygen was formed on the surface of a particle of a lithium nickel composite oxide as a coating covering the particle of the lithium nickel composite oxide.
[0138] The amount of carbon contained in the obtained positive electrode active material for a non-aqueous electrolyte secondary battery was measured by high-frequency combustion infrared absorption method using a carbon analyzer (manufactured by LECO, model number: CS-600) and was found to be 0.07% by mass.
[0139] In addition, the positive electrode active material for non-aqueous electrolyte secondary batteries was analyzed by ICP emission spectrometry, and it was confirmed that the boron content was below the detection limit, i.e., less than 0.01 mass%, and the silicon content was 0.07 mass%. (2) Evaluation results A coin cell (positive electrode / separator and electrolyte / negative electrode) was fabricated using the positive electrode active material for non-aqueous electrolyte secondary batteries as the positive electrode, and the charge / discharge characteristics were evaluated. The cell was charged to a cutoff voltage of 4.3 V at a C rate of 0.05 C, and then discharged to a cutoff voltage of 3.0 V. The charge capacity was confirmed to be 220 mAh / g and the discharge capacity was confirmed to be 192 mAh / g.
[0140] In addition, when the positive electrode resistance value was calculated in the same manner as above using the produced coin cell, it was confirmed to be 2.4 Ω.
[0141] Next, the positive electrode active material for non-aqueous electrolyte secondary batteries was placed in a Teflon container and left in a thermo-hygrostat set at a temperature of 80°C and a humidity of 60% for 24 hours. A coin cell (positive electrode / separator and electrolyte / negative electrode) was produced using this as the positive electrode, and the charge / discharge characteristics were evaluated in the same manner as above, confirming that the charge capacity was 210 mAh / g and the discharge capacity was 187 mAh / g.
[0142] In addition, the positive electrode resistance value was calculated in the same manner as above using the produced coin cell, and it was confirmed to be 3.6 Ω.
[0143] The production conditions and evaluation results are shown in Tables 1 and 2.
[0144] [Table 1]
[0145] [Table 2] It was confirmed that the coin cells using the positive electrode active materials for nonaqueous electrolyte secondary batteries produced in Examples 1 and 2 in the positive electrode had higher charge capacity and discharge capacity after the weather resistance test than the coin cell using the positive electrode active material for nonaqueous electrolyte secondary batteries in Comparative Example 1. That is, it was confirmed that the weather resistance of the positive electrode active material was improved by using a positive electrode active material having particles of lithium nickel composite oxide and a region containing boron, etc., and having a carbon content of 0.06 mass% or less, i.e., the deterioration of the charge / discharge characteristics due to exposure to a high-temperature and high-humidity environment could be suppressed.
[0146] In addition, when comparing corresponding examples and comparative examples, specifically, Example 1 and Comparative Example 2, and Example 2 and Comparative Example 3, which differ only in the presence or absence of heat treatment, it can be confirmed that the positive electrode active materials of Examples 1 and 2 have a carbon content of 0.06 mass% or less, while the positive electrode active materials of Comparative Examples 2 and 3 have a carbon content exceeding 0.06 mass%. It was confirmed that the coin cells using the positive electrode active materials of Examples 1 and 2, which have a carbon content of 0.06 mass% or less, have high charge capacity and discharge capacity even after the weather resistance test, compared with the coin cells using the positive electrode active materials of Comparative Examples 2 and 3, which have a carbon content exceeding 0.06 mass%. Furthermore, it was confirmed that the carbon content of the positive electrode active material can be reduced by performing the contact process. [Explanation of symbols]
[0147] 2. Lithium nickel composite oxide particles 4. One or more compounds selected from boron compounds, phosphorus compounds, and silicon compounds
Claims
1. General formula: Li x Ni 1―y―z Co y A z O 2 Particles of a lithium nickel composite oxide represented by the formula (0.90≦x≦1.20, 0.01≦y≦0.20, 0.01≦z≦0.10), and The lithium nickel composite oxide particle has a region disposed on at least a portion of a surface thereof, the region containing one or more elements selected from boron (B), phosphorus (P), and silicon (Si), lithium (Li), and oxygen (O); A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising: a carbon content of 0.06 mass % or less; and a boron (B) content of 0.01 mass % or more and 0.10 mass % or less.
2. General formula: Li x Ni 1―y―z Co y A z O 2 Particles of a lithium nickel composite oxide represented by the formula (0.90≦x≦1.20, 0.01≦y≦0.20, 0.01≦z≦0.10), and The lithium nickel composite oxide particle has a region disposed on at least a portion of a surface thereof, the region containing one or more elements selected from boron (B), phosphorus (P), and silicon (Si), lithium (Li), and oxygen (O); A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising: a carbon content of 0.06 mass % or less; and a silicon (Si) content of 0.05 mass % or more and 0.30 mass % or less.
3. General formula: Li x Ni 1―y―z Co y A z O 2 Particles of a lithium nickel composite oxide represented by the formula (0.90≦x≦1.20, 0.01≦y≦0.20, 0.01≦z≦0.10), and The lithium nickel composite oxide particle has a region disposed on at least a portion of a surface thereof, the region containing one or more elements selected from boron (B) and silicon (Si), lithium (Li), and oxygen (O); The boron (B) content is 0.01% by mass or more, or the silicon (Si) content is 0.05% by mass or more, A positive electrode active material for a non-aqueous electrolyte secondary battery, the positive electrode active material having a carbon content of 0.03% by mass or more and 0.06% by mass or less.
4. 3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the phosphorus (P) content is 0.01% by mass or more and 0.10% by mass or less.
5. 5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the lithium nickel composite oxide particles are composed of secondary particles formed by agglomeration of primary particles, and the average particle diameter of the secondary particles is 3 μm or more and 20 μm or less.
Citation Information
Patent Citations
Lithium ion conductive solid electrolyte composite body, and lithium cell
JP2003331912A
Cathode active material for nonaqueous electrolyte secondary battery and nonaqueous secondary battery using it
JP2008251480A
Positive electrode for nonaqueous electrolyte battery, method for manufacturing the same, and nonaqueous electrolyte battery
JP2010177024A
Positive electrode material for nonaqueous electrolyte lithium ion battery and battery using the same
JP2012084547A
Positive electrode active material for nonaqueous electrolyte secondary battery, method for manufacturing the same, and nonaqueous electrolyte secondary battery comprising the same
JP2013026199A
Cited By
Positive electrode active material for non-aqueous electrolyte secondary battery
JP2023168496A